IM-Vative sandbox: fun learning in mastering hypertext markup language (HTML) / Izzatil Husna Arshad ...[et al.] - Arshad, Izzatil Husna; Hamidon, Huda; Md Radzi, Salliza; Alias, Noor Rahmawati; Mohamad Rosman, Mohamad Rahimi; Chik, Nor Kamariah; Fadzil, Faizal Haini; Mohd Zawawi, Mohd Zafian; Radzlan, Noor Masliana; Abdul Hamid, Haslinda; Mohd Saleh, Mohd Idzwan (2020)
Hypertext Markup Language (HTML) is one of the most popular languages for website development. Since its inception, many academic institutions have integrated the knowledge of HTML within their syllabus. However, previous research shows that many students are having difficulties to be proficient in HTML language. Several problems are identified; (1) lack of effective online content, (2) lack of supporting tool to code HTML, (3) portability issue of authoring software. Therefore, IM-Vative Sandbox was developed based on PHP Programming Language (PHP), MySQL Database, and jQuery. The sandbox provides real-time generation of HTML source codes; compared to the conventional method of using Notepad, Sublime, or any other authoring tools. In terms of commercialization, the application can be accessed through mobile and desktop and suitable for beginners who want to learn the basics of HTML